2018
DOI: 10.1186/s12872-018-0950-x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin regulates atrial SK2 and SK3 expression through inhibiting the PKC/ERK signaling pathway in type 2 diabetic rats

Abstract: BackgroundOur previous study showed that metformin regulates the mRNA and protein levels of type 2 small conductance calcium-activated potassium channel (SK2) and type 3 small conductance calcium-activated potassium channels (SK3) in atrial tissue as well as the ion current of atrial myocytes in rats with type 2 diabetes mellitus (T2DM), but the underlying signaling mechanism is unknown. This study aimed to investigate whether metformin regulates atrial SK2 and SK3 protein expression in T2DM rats though the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Although glucose level remained stable at that level in batch 1, they declined over time in batch 2, reaching pre-dapagliflozin and end-of-study levels of about 200 mg/dl. Although the end-of-study glucose level in batch 1 was in line with reports of others in this model (Zhang et al, 2012; Lee et al, 2018; Li et al, 2018; Liu et al, 2018), those of batch 2 were not and probably cannot be considered diabetic but rather as mildly hyperglycemic. We consider a partial recovery of pancreatic beta cells after a less effective destruction by STZ (Desgraz et al, 2011; Cheng et al, 2016) as the most likely explanation for the decline of blood glucose in batch 2.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although glucose level remained stable at that level in batch 1, they declined over time in batch 2, reaching pre-dapagliflozin and end-of-study levels of about 200 mg/dl. Although the end-of-study glucose level in batch 1 was in line with reports of others in this model (Zhang et al, 2012; Lee et al, 2018; Li et al, 2018; Liu et al, 2018), those of batch 2 were not and probably cannot be considered diabetic but rather as mildly hyperglycemic. We consider a partial recovery of pancreatic beta cells after a less effective destruction by STZ (Desgraz et al, 2011; Cheng et al, 2016) as the most likely explanation for the decline of blood glucose in batch 2.…”
Section: Discussionsupporting
confidence: 89%
“…This combination is a routinely applied T2DM model (Zhang et al, 2012; Lee et al, 2018; Li et al, 2018; Liu et al, 2018). Although increased body weight is a typical feature of human T2DM, this is not mimicked by the HFD/STZ model (Zhang et al, 2012; Lee et al, 2018; Li et al, 2018; Liu et al, 2018) as confirmed in the present study. Therefore, our model does not recapitulate the obesity phenotype typically seen in T2DM and may include elements of a T1DM phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that the effects of lidocaine on CFA-induced rats were significantly reversed by rh-EGF. Since rh-EGF is an ERK agonist ( 43 ), data from the present study suggest that rh-EGF + lidocaine significantly reduced TWL, MWT and frequency responses to cold stimulation but significantly increased TNF-α, IL-1β and IL-6 levels through activating the ERK pathway.…”
Section: Discussionmentioning
confidence: 52%
“…Enhanced F-box protein 32 was associated with decreased SK2 protein expression [71]. Several studies have recently reported that metformin played a vital role in restoring the electrophysiology of SK channels [72][73][74].…”
Section: Anti-af Potential Of Sk Channel Inhibitorsmentioning
confidence: 98%